Factors associated with quality of life among family members of patients with dementia in Cyprus - Andreou, Panayiota; Middleton, Nicos; Papacostas, Savvas S.; Kyriacou Georgiou, Irini; Papastavrou, Evridiki (My University, 2014)
Background: Numerous studies have reported that caring for a person with dementia is a stressful experience. Nevertheless, quality of life (QoL) measures have commonly focused on patients, while factors that inﬂuence caregivers’ QoL have not been clearly identiﬁed. In order to contribute to the understanding of caregivers’ QoL, we explored how QoL among caregivers is related to their perceived level of burden, their reported number of depressive symptoms, and the level of care recipients’ dependency. Methods: Seventy-six caregivers referred by the two main referral centers of patients with dementia in Cyprus participated in a cross-sectional survey with a descriptive correlational design. Caregivers completed four instruments, measuring burden (ZBI), depression (CES-D), quality of life-Alzheimer’s disease (QoL-AD), and activities of daily living (ADL) of the care recipients and provided socio-demographic information. Results: The majority of the participants scored high levels of burden (M= 43.32/SD = 15.23) and depression (59.2% scored over the cut-off point of 16). QoL was only moderate (M = 30.89/SD = 8.21) and negatively correlated with burden (r = −32, p = 0.01) and depression (r = −0.296, p < 0.05). Only a weak correlation was observed between QoL and ADL (r= 0.167, p= 0.15). Hierarchical multiple regression analyses revealed that overall burden scores and income were associated with QoL, explaining 20% of the overall variance of the caregiver’s QoL. Conclusion: Further research is necessary to investigate which additional domains determine QoL and further our understanding of the factors that may reduce the burden imposed on dementia caregivers.
Keywords: Caregivers; Dementia; Quality of life